A surface strengthening material and its application
By using metal-ceramic composite powder material and cold spraying technology on complex parts of magnesium alloys, combined with ultra-high frequency induction heating, the problem of difficulty in preparing millimeter-level thickness coatings is solved, and high hardness and wear resistance are achieved surface reinforcement effect with corrosion resistance.
Patent Information
- Application Number
- CN202211433960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-16
AI Technical Summary
It is difficult to prepare protective coatings of millimeter-level thickness on complex parts of magnesium alloys in the prior art. Traditional cladding technology has problems such as pores, cracks, expensive equipment, and complex operation.
Using a metal-ceramic composite powder material, composed of Si3N4, Al2O3, Al-RE intermediate alloy and Al, it is sprayed to the surface of the part by cold spraying technology, and metallurgical cladding with a thickness of millimeters is formed under ultra-high frequency induction heating. layer.
The surface of magnesium alloy parts has been formed with high hardness, wear resistance and corrosion resistance, which significantly improves the service life of the parts.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of surface strengthening, and in particular relates to a surface strengthening material and application thereof, specifically a surface strengthening material and strengthening process suitable for complex magnesium alloy parts. Background Art
[0002] Magnesium alloy parts usually need to be surface treated before use to isolate the substrate from external corrosion, oxidation and other harsh environments. Common methods include electroplating, chemical plating, anodizing, organic coating dipping and other technologies to form one or more layers of protection. Since the protective layer is usually thin, if the metal itself does not have sufficient corrosion resistance, the parts may be scrapped in a very short time after the protective layer is damaged. If the coating is thick, its tolerance will be greatly improved. In actual application, magnesium alloy parts usually need to be protected on the surface to obtain a protective layer of other corrosion-resistant metals or ceramics on the surface. The thickness of the protective layer is usually around tens of microns, and no more than one hundred to two hundred microns at most. When the surface is hit or used for a long time in a corrosive environment, the coating is easily damaged, which seriously reduces the service life of the parts.
[0003] The existing methods for obtaining millimeter-level coatings on the surface of metal parts are mainly cladding technologies. Traditional cladding methods are not suitable for the preparation of millimeter-level coatings on complex parts. Cladding technologies mainly include laser cladding, thermal spraying, arc cladding and surfacing according to different heat sources. Porosity and cracks are prone to occur during laser cladding treatment, and the expensive price of laser equipment, complex processes and high requirements for the operating environment limit the application of laser cladding technology. Thermal spraying equipment is expensive and cannot complete the coating of parts with complex shapes. The powder surface bonding method is mechanical bonding, and the coating adhesion is low. Argon arc cladding is also not suitable for parts with complex shapes, and the appearance and morphology of the cladding layer are poor, and the microstructure morphology is difficult to control. Surfacing is only suitable for metal materials with a certain thickness, has certain requirements for the material, and the appearance and morphology are relatively poor. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a surface strengthening material and application thereof. The surface strengthening material provided by the present invention has good performance when used for part surface strengthening.
[0005] The present invention provides a surface strengthening material, the components of which are:
[0006] 20-50wt% Si3N4;
[0007] 20-40wt% Al2O3;
[0008] 1-50wt% Al-RE master alloy;
[0009] The balance is Al and inevitable impurities.
[0010] Preferably, the Si3N4 is powder; the size of the Si3N4 powder particles is 5nm to 500μm;
[0011] The Al2O3 is in powder form; the particle size of the Al2O3 powder is 5nm to 500μm;
[0012] The Al-RE master alloy is in powder form, and the particle size of the Al-RE master alloy powder is 5 nm to 500 μm;
[0013] The Al is in powder form; the particle size of the Al powder is 50 nm to 500 μm.
[0014] Preferably, the RE in the Al-RE master alloy is selected from one or more of La, Ce, Pr, Nd, Sm, Y, Gd, Er, Eu, Yb, Y, Dy, Ho, Lu, and Sc; and the mass content of the RE in the Al-RE master alloy is 1 to 80%.
[0015] The present invention provides a surface strengthening method, comprising:
[0016] ball-milling the surface strengthening material to obtain a ball-milled material;
[0017] The ball-milled material is sprayed onto the surface of the part by a cold spraying process to obtain a cold sprayed product;
[0018] heating the cold sprayed product to obtain a composite strengthening layer;
[0019] The surface strengthening material is the surface strengthening material described in the above technical solution.
[0020] Preferably, the ball milling is carried out in a ball milling jar; the ball milling method is dry ball milling; the ball-to-material ratio during the ball milling process is (3-7):1; the ball milling time is 8-12 hours; and the rotation speed during the ball milling process is 400-600 rpm.
[0021] Preferably, the accelerating gas in the cold spraying process is selected from one or more of nitrogen, argon and helium; the pressure of the accelerating gas is 2 to 10 MPa; the preheating temperature of the accelerating gas is 300 to 450°C; the moving speed of the spray gun is 50 to 500 mm / s; the spraying distance is 10 to 50 mm; and the thickness of the sprayed coating is 100 μm to 3 mm.
[0022] Preferably, the heating method is selected from one or more of laser heating, induction heating, and argon arc welding heating.
[0023] Preferably, the laser power in the laser heating process is 50-100 P / W; the scanning speed is 200-1000 mm / s; and the scanning interval is 40-100 μm.
[0024] Preferably, the current frequency of the hot furnace equipment in the induction heating process is 3000-8000 Hz; the loading current is 2000-10000 A; and the distance between the induction coils is 1 mm-2 cm.
[0025] Preferably, the travel speed during the argon arc welding heating process is 10 to 50 mm / s; the current is 100 to 200 A; and the flow rate of argon gas is 8 to 12 L / min.
[0026] The present invention provides a millimeter-level composite coating material and preparation method suitable for magnesium alloy parts. Since the thickness is much higher than that of traditional coatings, the life of magnesium alloy parts is significantly improved when they are used for a long time in harsh environments such as impact, corrosion, high temperature, cosmic rays, etc. The present invention is aimed at magnesium alloy parts, and proposes a surface cladding material and cladding method suitable for magnesium alloy systems. The metallurgical cladding layer with a thickness of millimeters is formed on the alloy surface by combining cold spraying with ultra-high frequency induction heating, which has the characteristics of simple operation, low cost and strong bonding force. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a surface strengthening material (metal-ceramic composite powder), the components of which are:
[0029] 20-50wt% Si3N4;
[0030] 20-40wt% Al2O3;
[0031] 1-50wt% Al-RE master alloy;
[0032] The balance is Al and inevitable impurities.
[0033] In the present invention, the mass content of the Si3N4 (ceramic) is preferably 30-40%, more preferably 35%.
[0034] In the present invention, the Si3N4 is preferably a powder; the size of the Si3N4 powder particles is preferably 5nm~500μm, more preferably 50nm~400μm, more preferably 100nm~300μm, more preferably 500nm~200μm, more preferably 1~150μm, more preferably 10~100μm, more preferably 20~80μm, more preferably 30~60μm, and most preferably 40~50μm.
[0035] In the present invention, the mass content of Al2O3 is preferably 25-35%, more preferably 30%.
[0036] In the present invention, the Al2O3 is preferably a powder; the size of the Al2O3 powder particles is preferably 5nm~500μm, more preferably 50nm~400μm, more preferably 100nm~300μm, more preferably 500nm~200μm, more preferably 1~150μm, more preferably 10~100μm, more preferably 20~80μm, more preferably 30~60μm, and most preferably 40~50μm.
[0037] In the present invention, the mass content of the Al-RE master alloy is preferably 10 to 40%, and more preferably 20 to 30%.
[0038] In the present invention, the RE is preferably selected from one or more of La, Ce, Pr, Nd, Sm, Y, Gd, Er, Eu, Yb, Y, Dy, Ho, Lu, and Sc; the mass content of the RE in the Al-RE master alloy is preferably 1 to 80%, more preferably 10 to 70%, more preferably 20 to 60%, more preferably 30 to 50%, and most preferably 40%.
[0039] In the present invention, the Al-RE (rare earth) intermediate alloy is preferably a powder, and the powder particle size of the Al-RE (rare earth) intermediate alloy is preferably 5nm~500μm, more preferably 50nm~400μm, more preferably 100nm~300μm, more preferably 500nm~200μm, more preferably 1~150μm, more preferably 10~100μm, more preferably 20~80μm, more preferably 30~60μm, and most preferably 40~50μm.
[0040] In the present invention, the Al is preferably a powder; the size of the Al powder particles is preferably 50nm to 500μm, more preferably 50nm to 400μm, more preferably 100nm to 300μm, more preferably 500nm to 200μm, more preferably 1 to 150μm, more preferably 10 to 100μm, more preferably 20 to 80μm, more preferably 30 to 60μm, and most preferably 40 to 50μm.
[0041] In the present invention, the mass content of the Si3N4 ceramic is preferably 20-50%, and the powder particle size is preferably 50nm-20μm; the mass content of the Al2O3 powder is preferably 20-40%, and the powder particle size is preferably 50nm-20μm; the mass content of RE in the Al-RE (rare earth) intermediate alloy powder is preferably 2-20%, and the mass content of the Al-RE (rare earth) intermediate alloy powder is preferably 2-30%; the size of the Al powder particles is preferably 10μm-70μm.
[0042] In the present invention, the preparation method of the surface strengthening material preferably comprises:
[0043] Si3N4, Al2O3, Al-RE master alloy and Al are mixed to obtain a surface strengthening material.
[0044] The present invention provides a surface strengthening method, comprising:
[0045] ball-milling the surface strengthening material to obtain a ball-milled material;
[0046] The ball-milled material is sprayed onto the surface of the part by a cold spraying process to obtain a cold sprayed product;
[0047] The cold sprayed product is heated to obtain a composite strengthening layer.
[0048] In the present invention, the ball milling is preferably carried out in a ball milling jar; the ball milling method is preferably dry ball milling; the ball-to-material ratio in the ball milling process is preferably (3-7):1, more preferably (4-6):1, and most preferably 5:1; the ball milling time is preferably 8-12 hours, more preferably 9-11 hours, and most preferably 10 hours; the rotation speed in the ball milling process is preferably 400-600 rpm, more preferably 450-550 rpm, and most preferably 500 rpm.
[0049] In the present invention, the cold spraying preferably further comprises:
[0050] The surfaces of the parts are polished, degreased, cleaned and dried in sequence.
[0051] In the present invention, the polishing is preferably sandpaper polishing; the cleaning is preferably acetone cleaning; and the drying is preferably cold air drying.
[0052] In the present invention, the parts are preferably magnesium alloy parts, such as AZ91 magnesium alloy, WE43 magnesium alloy, Mg-Gd-Y-Zn-Gd alloy, etc.
[0053] In the present invention, the accelerating gas in the cold spraying process is preferably selected from one or more of nitrogen, argon and helium; the pressure of the accelerating gas is preferably 2-10 MPa, more preferably 3-8 MPa, more preferably 4-6 MPa, and most preferably 5 MPa; the preheating temperature of the accelerating gas is preferably 300-450°C, more preferably 350-400°C, and most preferably 360-380°C; the moving speed of the spray gun is preferably 50-500 mm / s, more preferably 100-400 mm / s, and most preferably 200-300 mm / s; the spraying distance is preferably 10-50 mm, more preferably 20-40 mm, and most preferably 30 mm; the thickness of the sprayed coating is preferably 100 μm-3 mm, more preferably 500 μm-2 mm, and most preferably 1 mm.
[0054] In the present invention, the heating preferably uses an instantaneous heating source to heat the surface of the sprayed layer to melt the outer composite material layer to obtain a composite reinforcement layer.
[0055] In the present invention, the heating method is preferably selected from one or more of a laser heating method, an induction heating method, and an argon arc welding heating method.
[0056] In the present invention, the laser heating method preferably uses a solid laser to perform laser cladding on the surface of the part to achieve melting of the surface composite strengthening layer, and utilizes the in-situ reaction of the molten layer to form a thicker composite strengthening layer, and a ceramic phase is generated inside the composite strengthening layer; the laser power in the laser heating process is preferably 50-100P / W, more preferably 60-90P / W, and most preferably 70-80P / W; the scanning speed is preferably 200-1000mm / s, more preferably 300-800mm / s, more preferably 400-600mm / s, and most preferably 500mm / s; the scanning spacing is preferably 40-100μm, more preferably 50-90μm, more preferably 60-80μm, and most preferably 70μm.
[0057] In the present invention, the induction heating method is preferably an ultra-high frequency induction heating method, and the sprayed parts are preferably heated by an induction coil equipped with an ultra-high frequency induction power supply to achieve melting of the surface composite strengthening layer, and the in-situ reaction of the molten layer is utilized to form a thicker composite strengthening layer, and a ceramic phase is generated inside the composite strengthening layer; the current frequency of the hot furnace equipment in the induction heating process is preferably 3000-8000Hz, more preferably 4000-7000Hz, and most preferably 5000-6000Hz; the loading current is preferably 2000-10000A, more preferably 3000-8000A, more preferably 4000-6000A, and most preferably 5000A; the induction coil distance is preferably 1mm-2cm, more preferably 5mm-1.5cm, and most preferably 1cm.
[0058] In the present invention, the argon arc welding heating preferably uses argon arc welding equipment to coat the plate, the parts are connected to the "+ pole", the tungsten pole is connected to the "- pole", the power is turned on, the adjustment button of the welding machine control panel is set to the "welding, pulse-free, DC, continuous, water-cooled, TIG" gear, the output current is preset, the TIG welding gun is fixed on the automatic walking mechanism or mechanical arm of the submerged arc welding, the height of the tungsten pole to the surface of the specimen is preset to 2 mm, and the walking device is moved back and forth to ensure that the tungsten pole end walks in a straight line on the specimen and maintains the same height; the walking speed during the argon arc welding heating process is preferably 10-50 mm / s, more preferably 20-40 mm / s, and most preferably 30 mm / s; the current is preferably 100-200 A, more preferably 130-170 A, and most preferably 150 A; the flow rate of argon gas is preferably 8-12 L / min, more preferably 10 L / min.
[0059] The present invention designs a metal-ceramic composite powder material for the surface strengthening layer of millimeter-level magnesium alloy parts and a related preparation method. The surface cladding layer provided by the method of the present invention is thicker, and Al2RE, SiO2, and AlN compounds are generated in the surface cladding layer. Since the compounds are generated in situ, the mechanical properties are better and the protection ability of magnesium alloy parts is stronger.
[0060] The present invention designs a powder material that can react with the surface of the magnesium alloy and easily form a protective composite material layer for the magnesium alloy system. The material contains Al elements, rare earth elements and Si3N4 ceramics, and has high-temperature self-reaction characteristics. AlN hard particles are generated to increase the density and strength of the coating. In addition, under ultra-high frequency induction heating conditions, only the powder on the surface of the part and the extremely shallow surface of the magnesium alloy part melt, and there are diffusion reactions, solid solution reactions and compound reactions between the Al powder and the Mg alloy matrix, so that the alloy surface protective layer and the matrix have good metallurgical bonding, a transition layer is generated, and sufficient bonding force is generated between the protective layer and the alloy matrix. Rare earth elements play a role in refining the structure and improving the antioxidant capacity of the surface strengthening layer during the cladding process. The advantage of the method provided by the present invention is that the cold spraying technology is used to facilitate the spraying operation on the surface of complex parts. Compared with traditional cladding materials and technologies, the millimeter-level cladding layer prepared by the present invention has higher hardness, wear resistance and corrosion resistance.
[0061] Example 1
[0062] The designed powder composition, mass percentage of each component and particle size are as follows:
[0063] Si3N4 ceramics: 30% powder, powder particle size: 10μm;
[0064] Al2O3 powder: 30% powder, powder particle size: 6μm;
[0065] Al-30%Ce rare earth master alloy powder, the powder particle size is: 10μm; the master alloy powder accounts for 20% of the composite powder;
[0066] The remaining 20% is Al powder and inevitable impurities, and the particle size of the Al powder is 100 μm.
[0067] The following steps are used to strengthen the surface of AZ91 magnesium alloy:
[0068] Step 1: Put the powder into the ball mill and use dry ball milling with a ball-to-material ratio of 5:1, a ball milling time of 12 hours and a rotation speed of 600 rpm.
[0069] Step 2: The surface of the base of the parts that need surface strengthening is sanded, degreased, cleaned with acetone, and dried with cold air.
[0070] Step 3: Use cold spraying process to spray the composite material powder onto the surface of the part, where the cold spraying accelerating gas is argon, the gas pressure is 5MPa, the gas preheating temperature is 300℃, the moving speed of the spray gun is 50mm / s, the spraying distance range is 15mm~30mm, and the average thickness of the spray layer is 1mm.
[0071] Step 4: Use a solid laser to perform laser cladding on the surface of the part to achieve melting of the surface composite strengthening layer, and use the in-situ reaction of the molten layer to form a thicker composite strengthening layer, and generate a ceramic phase inside the composite strengthening layer; the laser power is 60P / W, the scanning speed range is 450mm / s, and the scanning spacing is 40μm.
[0072] Example 2
[0073] The designed powder composition, mass percentage of each component and particle size are as follows:
[0074] Si3N4 ceramics: 40% powder, powder particle size: 70nm;
[0075] Al2O3 powder: 10% powder, powder particle size: 10μm;
[0076] Al-30%Ce rare earth master alloy powder, the powder particle size is: 10μm; the master alloy powder accounts for 20% of the composite powder;
[0077] The remaining 30% is Al powder and inevitable impurities, and the particle size of the Al powder is 100 μm.
[0078] The following steps are used to strengthen the surface of WE43 magnesium alloy:
[0079] Step 1: Put the powder into the ball mill and use dry ball milling with a ball-to-material ratio of 5:1, a ball milling time of 10 hours and a rotation speed of 500 rpm.
[0080] Step 2: The surface of the base of the parts that need surface strengthening is sanded, degreased, cleaned with acetone, and dried with cold air.
[0081] Step 3: Use cold spraying process to spray the composite material powder onto the surface of the part, where the cold spraying accelerating gas is argon, the gas pressure is 6MPa, the gas preheating temperature range is 400℃, the moving speed of the spray gun is 60m / s, the spraying distance range is 20m, and the average thickness of the spray layer is 2mm.
[0082] Step 4: Use an induction coil equipped with an ultra-high frequency induction power supply to heat the sprayed parts to achieve melting of the surface composite strengthening layer, and use the in-situ reaction of the molten layer to form a thicker composite strengthening layer, and generate a ceramic phase inside the composite strengthening layer; the equipment current frequency of the hot furnace is 6000Hz, the loading current is 3000A, and the induction coil distance range is 2mm.
[0083] Example 3
[0084] The designed powder composition, mass percentage of each component and particle size are as follows:
[0085] Si3N4 ceramics: 20% powder, powder particle size: 10μm;
[0086] Al2O3 powder: 20% powder, powder particle size: 10μm;
[0087] Al-30%Ce rare earth master alloy powder, the powder particle size is: 10μm; the master alloy powder accounts for 10% of the composite powder;
[0088] The remaining 50% is Al powder and inevitable impurities, and the particle size of the Al powder is 100 μm.
[0089] The following steps are used to strengthen the surface of Mg-Gd-Y-Zn-Gd alloy:
[0090] Step 1: Put the powder into the ball mill and use dry ball milling with a ball-to-material ratio of 5:1, a ball milling time of 12 hours and a rotation speed of 600 rpm.
[0091] Step 2: The surface of the base of the parts that need surface strengthening is sanded, degreased, cleaned with acetone, and dried with cold air.
[0092] Step 3: Use cold spraying process to spray the composite material powder onto the surface of the part, where the cold spraying accelerating gas is argon, the gas pressure is 10MPa, the gas preheating temperature is 300℃, the moving speed of the spray gun is 50mm / s, the spraying distance is 2mm; the average thickness of the spray layer is 2mm.
[0093] Step 4: Use argon arc welding equipment to coat the plate: connect the magnesium alloy part to the "+" pole, connect the tungsten pole to the "-" pole, turn on the power, set the adjustment button of the welding machine control panel to the "welding, pulse-free, DC, continuous, water-cooled, TIG" gear, pre-adjust the output current, fix the TIG welding gun on the automatic walking mechanism or mechanical arm of the submerged arc welding, pre-adjust the height from the tungsten pole to the surface of the specimen to 2mm, and move the walking device back and forth to ensure that the tungsten pole tip walks straight on the specimen and maintains the same height. Among them, the walking speed is 10mm / s, the current range is 100A, and the flow rate of argon gas is 10L / min.
[0094] Performance Testing
[0095] The surface hardness of the matrix and the strengthening layer was tested. The test method was as follows: the hardness test was carried out on a Vickers hardness tester, the load was 200g, the loading time was 15s, and the sample was strictly cut into a rectangular block specimen using an EDM CNC wire cutting machine (DK7732B-CG, Zhaoming CNC Equipment, China). The cut sample was polished with fine sandpaper; when conducting the hardness test, 12 positions were evenly selected on the sample surface for testing to ensure the accuracy of the experimental data; when calculating the data, the minimum and maximum values in the data must be removed, and the average value of the remaining experimental data is the final hardness value of the sample. The test results are as follows:
[0096] Matrix hardness HV Surface strengthening layer hardness HV Example 1 75 168 Example 2 92 182 Example 3 96 191
[0097] The present invention designs a metal-ceramic composite powder material for the surface strengthening layer of millimeter-level magnesium alloy parts and a related preparation method. The surface cladding layer provided by the method of the present invention is thicker, and Al2RE, SiO2, and AlN compounds are generated in the surface cladding layer. Since the compounds are generated in situ, the mechanical properties are better and the protection ability of magnesium alloy parts is stronger.
[0098] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.
Claims
1. A surface strengthening method, comprising: ball-milling the surface strengthening material to obtain a ball-milled material; The ball-milled material is sprayed onto the surface of the magnesium alloy part by a cold spraying process to obtain a cold sprayed product; the accelerating gas in the cold spraying process is selected from one or more of nitrogen, argon and helium; the pressure of the accelerating gas is 2-10 MPa; the preheating temperature of the accelerating gas is 300-450° C.; the moving speed of the spray gun is 50-500 mm / s; the spraying distance is 10-50 mm; and the thickness of the sprayed coating is 1 mm-3 mm; The cold sprayed product is heated to obtain a composite strengthening layer; Al2RE, SiO2, and AlN compounds are generated in situ in the composite strengthening layer; The surface strengthening material comprises: 20-50wt% Si3N4; the Si3N4 is powder; the particle size of the Si3N4 powder is 5nm-500μm; 20-40wt% Al2O3; the Al2O3 is powder; the particle size of the Al2O3 powder is 5nm-500μm; 1-50wt% Al-RE master alloy; the Al-RE master alloy is powder, and the particle size of the powder of the Al-RE master alloy is 5nm-500μm; RE in the Al-RE master alloy is selected from one or more of La, Ce, Pr, Nd, Sm, Y, Gd, Er, Eu, Yb, Dy, Ho, Lu, and Sc; the mass content of RE in the Al-RE master alloy is 1-80%; The balance is Al and inevitable impurities; the Al is in powder form; the particle size of the Al powder is 50nm~500μm; The heating method is selected from one or more of laser heating, induction heating, and argon arc welding heating; The laser power during the laser heating process is 50-100 P / W; the scanning speed is 200-1000 mm / s; the scanning spacing is 40-100 μm; The current frequency of the hot furnace equipment in the induction heating process is 3000~8000Hz; the loading current is 2000~10000A; the induction coil distance is 1mm~2cm; The travel speed during the argon arc welding heating process is 10-50 mm / s; the current is 100-200 A; and the flow rate of argon gas is 8-12 L / min.
2. The method according to claim 1, characterized in that The ball milling is carried out in a ball milling jar; the ball milling method is dry ball milling; the ball-to-material ratio during the ball milling process is (3-7):1; the ball milling time is 8-12 hours; and the rotation speed during the ball milling process is 400-600 rpm.
Citation Information
Patent Citations
Cold-spraying aluminum-base corrosion-resistant coating and preparation method thereof
CN105543835A
High-energy auxiliary spraying method and spraying system
CN112662987A
Turbine blade coating composition
US10041361B2